PERENCANAAN BENDUNG TETAP UNTUK JARINGAN IRIGASI BANDA MUSAJIK D.I GUMARANG KECAMATAN PELEMBAYAN KABUPATEN AGAM - Dodi Dodi; Masril Masril; Ana Susanti Yusman (Ensiklopedia Research and Community Service Review, 2023)
Banda Musajik, which is located in Jorong Alahan Anggang, Nagari Tigo Koto Silungkang, Agam Regency, West Sumatra Province, is one of the irrigation networks in D.I Gumarang, under the authority of the UPTD Balai SDA and BK North Sumatra Province. The service area is 30 ha, the water source comes from Batang alahan anggang. Weir planning is based on the design flood discharge with a return period of 100 years. The discharge plan uses 10 years of rainfall data. Rainfall stations that affect the Alahan Anggang watershed are Gumarang Station and Kampuang IV Station. The area's average rainfall was determined by the Thiessen Polygon method, the planned rain by the log normal method and the frequency analysis test using the chi square test. Maximum flood discharge (Q100) 13.54 m3/s. The effective width of the dam is 11.42 m, one flush door is 0.80 m wide, one pillar is 0.50 m thick. The type of lighthouse is round with a radius of 0.80 m and a height of 1.52 m. The stilling pool is planned for the Vlugter type with the height of the weir, the length of the pool floor and the radius of the weir of 3.74 m. The length of the flood embankment from the weir to the upstream is 19 m with a height of 0.50 m from the flood water level. From the analysis of the forces acting on the body of the weir, the number of vertical forces (ΣRV) is 5,916 T, the number of horizontal forces (ΣRH) is 8,397 T, the number of holding moments (ΣMT) is 352,678 T.m, the number of overturning moments (ΣMG) is 344,87 T.m. stability of the weir body against overturning 1.31 1.3 , against shear 1.42 1.3, Eccentricity ( e ) 5.05 78.74 Maximum stress 1.90 78.74, minimum stress -0.36 78.7, the design of the weir body is safe against shearing, overturning, and the bearing capacity of the ground.Key words : Hydrological analysis, Hydraulic design of weir, Weir stability.